Corporate sustainability disclosure on social media and its difference from sustainability reports:Evidence from the energy sector - Zhong, Ma; Wang, Mingyue (Frontiers in Environmental Science, 2023)
The purpose of this study is to examine the sustainability information that energy companies provide on social media and the relationship between that data and that which is shared in conventional sustainability reports. Based on stakeholder theory, we use a sample of Chinese A-share listed energy corporations in 2020 and refer to GRI G4 guidelines to conduct content analysis on their 17,451 tweets from the WeChat platform and 53 sustainability reports. The analysis results show the following: 1) both the sustainability disclosures of Chinese energy firms on WeChat platform and sustainability reports focus on investor and employee dimensions. Among them, the average proportion of investor dimension disclosure to total disclosure is 31.92% and 35.19% on social media and sustainability reports, respectively, and the average proportion of employee dimension disclosure is 27.22% and 17.92%, respectively. However, the two channels show a large difference in the environment and government dimensions. The average proportion of environment disclosure in sustainability reports is 13.44%, while on social media it is only 2.01%. Government disclosure in sustainability reports is 8.24% and as high as 20.43% on social media. (2) Chinese energy firms prefer to provide supplementary information on social media. For example, using the investor dimension as an example, the average proportion of non-GRI information on social media is 71.47%, while that of the sustainability report is only 48.56%. This study helps stakeholders to better understand sustainable information on social media.